A Dynamic Panel Approach to Measuring the Impact of Economic Complexity on Economic Growth at The Territorial Level in Romania - Anca Otilia DODESCU; Elena-Aurelia BOTEZAT; Alexandru CONSTANGIOARA (Communications of International Proceedings, 2022)
Economic complexity is considered an essential determinant of economic growth. Our research follows the ”Product Space” methodology to compute an index for the Economic Complexity of Romanian territorial units. A Romanian panel dataset is being analyzed using a system GMM approach to investigate the impact of economic complexity and exports on economic growth. Both short and long-run estimates are obtained for the exogenous variables. Results support our research hypotheses, documenting that economic complexity serves as a significant contributor to wealth at the territorial level. Most importantly, our findings advocate the necessity to conceive strategies to foster the development of economic complexity.
Keywords: Economic Complexity; Economic Growth; Product Space; Panel Analysis; Romanian territorial units.